1986
DOI: 10.1016/s0140-1971(86)80037-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ego and moral development in adolescents: a longitudinal study

Abstract: A longitudinal study was designed to examine the relation between Loevinger's measure of ego development and moral development as indexed by Rest's Defining Issues Test in a sample of 123 adolescents at 12 to 14 years of age and four years later. Study I assessed differential rates of change and theoretically predicted directions of change in the two developmental functions and gender differences in ego development. Substantial ego stage movement occurred (60 per cent advancement, 40 per cent stability); moral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 34 publications
5
20
0
Order By: Relevance
“…The present findings and the findings from other studies (e.g., Avery & Ryan, 1988;Gfellner, 1986; for an overview see Cohn, 1998) indicate the Self-Protective ego level to be the modal level in the early adolescence period. According to the revised description of ego development, the most important aspect of the transition from the Impulsive to the Self-Protective ego level is the reversal of a basically dependent attitude toward a basically independent attitude (Westenberg, Jonckheer, et al, 1998).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The present findings and the findings from other studies (e.g., Avery & Ryan, 1988;Gfellner, 1986; for an overview see Cohn, 1998) indicate the Self-Protective ego level to be the modal level in the early adolescence period. According to the revised description of ego development, the most important aspect of the transition from the Impulsive to the Self-Protective ego level is the reversal of a basically dependent attitude toward a basically independent attitude (Westenberg, Jonckheer, et al, 1998).…”
Section: Discussionsupporting
confidence: 81%
“…A good relationship is defined by the sharing of innermost feelings and thoughts. Empirical studies have indicated that the Self-Aware ego level is very rare in early adolescence, and the higher ego levels (see Table 1) are not at all relevant to young adolescents (e.g., Avery & Ryan, 1988;Cohn, 1998;Gfellner, 1986;Westenberg & Block, 1993).…”
Section: The Loevinger Conception Of Ego Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have examined gender comparisons in ego development during the adolescent and young adult years. Research suggests that during the high school years both girls and boys cluster around the Conformist and Self‐Aware stages, with most of the distribution falling between the Self‐Protective (E3) and Conscientious (E6) stages (Gfellner, 1986; Westenberg & Gjerde, 1999). Gender differences have been consistently found, with girls demonstrating higher ego development through high school (Cohn, 1991: Gfellner, 1986; Mabry, 1993).…”
Section: Empirical Research On Ego Development In Adolescencementioning
confidence: 99%
“…Research suggests that during the high school years both girls and boys cluster around the Conformist and Self‐Aware stages, with most of the distribution falling between the Self‐Protective (E3) and Conscientious (E6) stages (Gfellner, 1986; Westenberg & Gjerde, 1999). Gender differences have been consistently found, with girls demonstrating higher ego development through high school (Cohn, 1991: Gfellner, 1986; Mabry, 1993). Research suggests, however, that by the time children leave adolescence and move into young adulthood, there are no significant differences between the sexes (Bursik, 1995; Redmore, 1983).…”
Section: Empirical Research On Ego Development In Adolescencementioning
confidence: 99%